Clinical effects of COVID-19 vaccines on chronic spontaneous urticaria patients: a study on two Turkish centers - Kartal, Demet; Orujova, Shahzada; Ertaş, Ragıp (Frontiers in Medicine, 2023)
Background The relationship between CSU and vaccines is reported in the literature. The post-vaccine clinical effect of covid 19 vaccines on CSU patients is still unclear. we aimed to evaluate clinical effects of COVID 19 Vaccines on CSU patients. Materyal method CSU patients under treatment and follow-up in our outpatient clinic were evaluated retrospectively. To determine disease activity the urticaria activity score over seven days (UAS7) was used. The details of demographic information, CSU treatment, history of COVID 19 infection and exacerbation of urticaria during infection, COVID-19 vaccinations, type of vaccine, side effect reaction time after vaccination, hospital admission requirement were also assessed. Results Total of 190 patients with a mean age of The mean age of patients was 41,7±14,0 years (range = 18-72) were enrooled. The patient sample consisted of 50 males and 140 females (male/female ratio 1:2.8). 181(CoronaVac 77, Pfizer-BioNTech 104) patients were vaccinated. Urticarial exacerbation was occurred in 25 patients. The median UAS value was 5 before vaccination, it was 12 in patients with post-vaccine urticaria. Two patients had angioedema and one patient had anaphylaxis after vaccinated with Pfizer-BioNTech. Conclusion COVID-19 vaccination in the CSU can be considered safe. Cases with urticarial exacerbation appear to be transient and can be managed by antihistamine and/or systemic steroid therapies. More extensive studies are needed for the relationship with CSU and post-coronavirus vaccination anaphylaxy.